Polymorphisms and mutations in the melanocortin-3 receptor and their relation to human obesity - Demidowich, Andrew P. (Biochim Biophys Acta, 2017)
Inactivating mutations in the melanocortin 3 receptor (Mc3r) have been described as causing obesity in mice, but the physiologic effects of MC3R mutations in humans have been less clear. Here we review the MC3R polymorphisms and mutations identified in humans, and the in vitro, murine, and human cohort studies examining their putative effects. Some, but not all, studies suggest that the common human MC3R variant T6K+V81I, as well as several other rare, function-altering mutations, are associated with greater adiposity and hyperleptinemia with altered energy partitioning. In vitro, the T6K+V81I variant appears to decrease MC3R expression and therefore cAMP generation in response to ligand binding. Knockin mouse studies confirm the T6K+V81I variant increases feeding efficiency and the avidity with which adipocytes derived from bone or adipose tissue stem cells store triglycerides. Other MC3R mutations occur too infrequently in the human population to make definitive conclusions regarding their clinical effects.